2004
DOI: 10.1016/j.febslet.2004.10.072
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling of GPCR and RhoA‐induced Ca2+‐sensitization of chicken amnion smooth muscle lacking CPI‐17

Abstract: Ca2+ -sensitization of smooth muscle occurs through inhibition of myosin light chain phosphatase (MLCP) leading to an increase in the MLCK:MLCP activity ratio. MLCP is inhibited through phosphorylation of its regulatory subunit (MYPT-1) following activation of the RhoA/Rho kinase (ROK) pathway or through phosphorylation of the PP1c inhibitory protein, CPI-17, by PKC d or ROK. Here, we explore the crosstalk between these two modes of MLCP inhibition in a smooth muscle of a natural CPI-17 knockout, chicken amnio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 35 publications
(48 reference statements)
3
16
0
Order By: Relevance
“…This speculation is in keeping with the observation that Rho-kinase is important for lung morphogenesis during fetal life (24). Aside from the RhoA/Rho-kinase, inhibition of the MLCP has been reported to occur through CPI-17-dependent phosphorylation via PKC␦ (31). This inhibitory pathway is independent of the Rho/Rhokinase but is believed to only play a minor role in the G protein-coupled mechanism of Ca 2ϩ sensitization (30).…”
Section: Discussionsupporting
confidence: 71%
“…This speculation is in keeping with the observation that Rho-kinase is important for lung morphogenesis during fetal life (24). Aside from the RhoA/Rho-kinase, inhibition of the MLCP has been reported to occur through CPI-17-dependent phosphorylation via PKC␦ (31). This inhibitory pathway is independent of the Rho/Rhokinase but is believed to only play a minor role in the G protein-coupled mechanism of Ca 2ϩ sensitization (30).…”
Section: Discussionsupporting
confidence: 71%
“…In line with this possibility, recent reports have shown that the contractility of cultured VSMCs display a greater dependency than fresh tissue on the RhoA-ROCK pathway (3). Moreover, the phosphorylation site on MYPT1 changes upon culturing (53). Mature VSMCs are in a quiescent contractile phenotype under physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in vertebrates, myosin phosphatase (MYPT1-PP1) is selectively inhibited by the protein CPI-17, which does not inhibit other holoenzyme forms of PP1, such as glycogen-associated phosphatase (GM-PP1) . Phosphorylation of Thr38 in CPI-17 increases its inhibitory potency .1000-fold (Eto et al 1999), and smooth muscle contracts in response to hormones that trigger CPI-17 phosphorylation in a process called calcium sensitization (Stevenson et al 2004). Inhibitor-2 (I-2) is the most ancient of the PP1 inhibitor proteins and is conserved among all eukaryotes, from GLC8 in yeast to I-2 in Caenorhabditis elegans, Drosophila, Xenopus, and humans (Gruppuso et al 1985;Roach et al 1985;Tunget al 1995;Li et al 2007).…”
mentioning
confidence: 99%